Teknik dan Ekspresi sebagi Upaya Penguasaan Kualitas Gerak Tari Topeng Tunggal Betawi Menurut Perspektif Margaret N.H'Doubler - Alvianisa, Monik; Nursilah; Ida Bagus Ketut Sudiasa (Program Studi Pendidikan Tari FBS UNJ, 2023)
This study examines the problem of mastering the movement quality of the Single Mask Dance because this dance has a fairly high level of complexity. The purpose of this study was to determine the form of presentation, movement techniques, and movement quality of the Single Mask Dance through Technique and Expression according to Margaret N H'Doubler's perspective. This research can be used as an opportunity for further study regarding the mastery of movement quality in other types of dance using Technique and Expression theory. The research method used is descriptive qualitative analysis and data collection techniques through interviews, observations, literature studies, and document studies. The data obtained includes: 1) the form of presentation of the Single Mask Dance which can be seen through the analysis of the structure of the movement, 2) the movement technique which includes three aspects, namely the regulation of breath, energy, and rhythm, 3) the expression presented through the movement of the mask and body movements. The results of the analysis and interpretation of the data explain that the Single Mask Dance fulfills all sub-chapters in Technique and Expression. Thus, it can be concluded that Technique and Expression can be used as an effort to master the Single Mask Dance.